2012
DOI: 10.1515/jpem.2011.408
|View full text |Cite
|
Sign up to set email alerts
|

Congenital hypothyroidism

Abstract: Congenital hypothyroidism (CH) is defined as thyroid hormone deficiency present at birth. Babies with CH who are not identified and treated promptly develop severe mental retardation. Most of the babies with CH do not manifest the typical known signs and symptoms of hypothyroidism, and this is most likely due to transplacental passage of some maternal thyroid hormone in addition to some residual neonatal thyroid function, as might be seen with thyroid hypoplasia, an ectopic gland, or mild dyshormonogenesis. Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 0 publications
0
27
0
3
Order By: Relevance
“…The reported recall neonates with borderline or abnormal initial TSH values for serum TSH and T4 determination varies from 0.16 to 3.3% between different populations [1416]. Our recall rate of 0.18% is in the lower ranges.…”
Section: Discussionmentioning
confidence: 70%
“…The reported recall neonates with borderline or abnormal initial TSH values for serum TSH and T4 determination varies from 0.16 to 3.3% between different populations [1416]. Our recall rate of 0.18% is in the lower ranges.…”
Section: Discussionmentioning
confidence: 70%
“…CH occurs 1 in 3000 to 4000 live-births, 85% of which are due to thyroid dysgenesis and 15% due to inborn errors of thyroid metabolism 4. Thyroid hormone is important for the maturation of many target tissues and key for brain and skeletal development.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Lowering of TSH cutoff point is one of the most important causes of the increasing recall rate. Evidences showed that the recall rate is one of the crucial indicators of screening cost-effectiveness and implementation capability.…”
Section: Discussionmentioning
confidence: 99%